2021
DOI: 10.1186/s13287-021-02641-x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood plasma-derived exosomes as a novel therapy to reverse liver fibrosis

Abstract: Background Cirrhosis is a chronic liver disease whereby scar tissue replaces healthy liver parenchyma, leading to disruption of the liver architecture and hepatic dysfunction. Currently, there is no effective disease-modifying therapy for liver fibrosis. Recently, our group demonstrated that human umbilical cord blood (UCB) plasma possesses therapeutic effects in a rat model of acute liver failure. Methods In the current study, we tested whether ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Similarly, hUCMSC-derived EVs have provided evidence of their ability to accelerate the functional and morphological recovery of cisplatin-induced acute kidney injury by promoting proliferation and damage repair once incorporated into damaged epithelium, a result that has been observed both in vitro and in vivo [142]. Interestingly, IVadministered hWJMSC-derived EVs preserved kidney function and decreased serum levels of the AKI marker neutrophil gelatinase-associated lipocalin in a unilateral kidney ischemia model [143], and hUBCMSC-derived EVs are instead suggested for the treatment of liver fibrosis [144]. Furthermore, hUCBMSC-derived EVs improve dextran sulfate sodium-induced inflammatory bowel disease through the modulation of IL-7 expression in macrophages [145], whereas by inhibiting inflammatory cell migration into the eye, they ameliorate the autoimmune disease uveoretinitis [146].…”
Section: Umbilical Cord-derived Evsmentioning
confidence: 96%
“…Similarly, hUCMSC-derived EVs have provided evidence of their ability to accelerate the functional and morphological recovery of cisplatin-induced acute kidney injury by promoting proliferation and damage repair once incorporated into damaged epithelium, a result that has been observed both in vitro and in vivo [142]. Interestingly, IVadministered hWJMSC-derived EVs preserved kidney function and decreased serum levels of the AKI marker neutrophil gelatinase-associated lipocalin in a unilateral kidney ischemia model [143], and hUBCMSC-derived EVs are instead suggested for the treatment of liver fibrosis [144]. Furthermore, hUCBMSC-derived EVs improve dextran sulfate sodium-induced inflammatory bowel disease through the modulation of IL-7 expression in macrophages [145], whereas by inhibiting inflammatory cell migration into the eye, they ameliorate the autoimmune disease uveoretinitis [146].…”
Section: Umbilical Cord-derived Evsmentioning
confidence: 96%
“…found that UCB-EXO also exert antifibrotic effects in a mouse model of LF. The mechanism may be that UCB-EXO inhibit the TGF-β-ID1 signaling pathway to block HSC activity ( 81 ).…”
Section: Clinical Application Of Exosomes In Lfmentioning
confidence: 99%
“…Xiao et al (2019b) reported that serum exosomal lncRNA-H19 promoted HF via the S1PR2/SphK2 and let-7/HMGA2 pathways, indicating that serum exosomal lncRNA-H19 may represent a novel therapeutic target for cholestatic HF. A separate study (Huang et al, 2021) found that upregulation of matrix metalloproteinases (MMP-2, MMP-9, MMP-13) in human umbilical cord blood plasma-derived exosomes (hUCB-exos) inhibited the accumulation of ECM and the progression of HF. Note: HF, hepatic fibrosis; MSC, mesenchymal stem cell; hESC, human embryonic stem cell; HLSC, human liver stem cell; HEK293T, human embryonic kidney cell; NK, cell, natural killer cell; HSC, hepatic stellate cell.…”
Section: Figurementioning
confidence: 99%